Diskriminasi Gender dalam Novel Ginko Karya Junichi Watanabe - Unsriana, Linda (Lingua Cultura, 2014)
Discrimination is an attitude and behavior that violates human rights. Discrimination can also be interpreted as a treatment for individuals differently based on race, religion, or gender. Any harassment, restriction, or exclusion to race, religion, or gender includes discriminatory actions. The theme of discrimination experienced by many women made the writer want to examine it from literature point of view, especially Japanese literature. The problem in this paper is gender discrimination experienced by the main character in novel Ginko. In Ginko novel written by Junichi Watanabe, the theme of discrimination against women is very strong, as experienced by the main character named Gin Ogino. This study used feminist standpoint research with the assumption that gender discrimination in society in the novel cannot be separated from women’s real experiences perceived by the author. In addition to stand on or derived from real experiences from the first woman doctor in Japan, which with all her efforts to break away from discrimination against women endured throughout her life: before marriage, divorce, attending medical school to become a doctor, even after she was graduated from medical school, she still experienced gender discrimination. This study found that gender discrimination experienced by Ginko because she is a woman, in which at that time (the Meiji era) there were clear boundaries between men and women. Difficulty and discrimination experienced are because Ginko’s ideals were considered impossible, because she wanted to become a doctor. Her ability and cleverness were obstructed just because she is a woman. It can be concluded in the Meiji era, there was discrimination against women reflected in the Novel Ginko.